Parallel Bessel beam arrays generated by envelope phase holograms. (February 2023) - Zhai, Zhongsheng; He, Xuan; Yu, Xin; Liu, Da; Lv, Qinghua; Xiong, Zhi; Wang, Xuanze; Xu, Zhongbao
Highlights: Envelope phase method is presented to generate parallel Bessel arrays with high SNR. The calculation method of the incomplete axicon phase holograms is deduced. Three different methods for generating Bessel arrays are proposed. The number, length and axial intensity distribution of the Bessel arrays can be adjusted by the programmable SLM. Abstract: Bessel beam arrays have important applications in ultra-laser processing, but most of its implementation methods have the disadvantages of complex process, high cost or poor effect. In this paper, a Bessel beam array generation method is proposed based on envelope phase holograms. Applying the programmable characteristics of spatial light modulator (SLM), the parallel Bessel beam array with adjustable spacing, quantity and intensity is simulated. The diffraction pattern of the Bessel array is discussed based on the angular spectrum diffraction theory. The phase expression of the envelope superposition morphology is deduced based on the analysis of the transmission function of the axicon. Three different methods are introduced and the quality of the arrays generated by these methods are compared. Simulation and experimental results show that the diffraction pattern of Bessel beam array generated by the envelope phase holograms can keep the Bessel beams as parallel with high signal noise ratio. The research of this paper will provide a theoretical basis for the development and application of the parallel Bessel beam array.